Living (with) Ice: Geo-sociality in the High Arctic - Hastrup, Kirsten (Journal of Northern Studies, 2021)
The main tenet of this article is to show how the ice, so visually dominant in the High Arctic, is also a prominent life force. The ice is never still and as it moves, melts or freeze, it deeply affects human and animal life in the region; conversely the diverse life-forms affect the icy environment in their own way and tempo. This interplay exposes the geo-social relations at the centre of this article, taking off from the gradual retraction of the ice after the last Ice Age, opening up for human movement and settlement in High Arctic America and eventually in Thule (Avanersuaq), in Northwest Greenland. Today some 750 people live there as hunters in the unsurpassable old hunting style, yet also as modern as anybody when it comes to outlook. Through brief discussions of particular periods, from the “discovery” of the Inughuit in 1819 and until the present, it is shown how deeply their life is implicated in the living ice, for better and for worse. The ice emerges as a refrain that holds the landscape together. The argument is based both in historical research and in regular anthropological fieldwork in the region over ten years 2007–2017.